2010
DOI: 10.1111/j.1743-6109.2010.01778.x
|View full text |Cite
|
Sign up to set email alerts
|

ORIGINAL ARTICLES: Definitions/Epidemiology/Risk Factors for Sexual Dysfunction

Abstract: A review of the currently available evidence from epidemiological studies is provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
474
4
37

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 727 publications
(532 citation statements)
references
References 32 publications
17
474
4
37
Order By: Relevance
“…11-31%). [1][2][3][4][5][6][7][8][9] Since the fourth edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-IV), the diagnosis of a sexual dysfunction is based on the presence of both a sexual impairment and distress due to this impairment. 10 Only a few epidemiological studies to date have included the assessment of sexual distress.…”
Section: Introductionmentioning
confidence: 99%
“…11-31%). [1][2][3][4][5][6][7][8][9] Since the fourth edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-IV), the diagnosis of a sexual dysfunction is based on the presence of both a sexual impairment and distress due to this impairment. 10 Only a few epidemiological studies to date have included the assessment of sexual distress.…”
Section: Introductionmentioning
confidence: 99%
“…ЕД трапляється у 50-60 % чоловіків, які страждають від ЦД [19]. В іншому дослідженні ЕД виявлялася у 49 % чоловіків, хворих на ЦД 1-го типу [25], у той час як серед чоловіків з ЦД 2-го типу цей показник досягав 89,2 % [25]. При обстеженні хворих, які перебували на стаціонарному лікуванні з приводу ЦД, автори відзначали частоту ЕД від 23 до 59 % [26].…”
Section: ключові слова: цукровий діабет; еректильна дисфункція; глікоunclassified
“…5 Erectile dysfunction (ED) is defined as the inability to achieve or maintain an erection sufficient for satisfactory sexual intercourse and is the most common sexual problem among aging male subjects. 6,7 The Massachusetts Male Aging Study reported that 52% of their community-based survey of men aged between 40 and 70 years old suffered from some degree of ED. 7 ED has been demonstrated to have a negative impact on intimate relationships, quality of life 8 and self-esteem.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 The Massachusetts Male Aging Study reported that 52% of their community-based survey of men aged between 40 and 70 years old suffered from some degree of ED. 7 ED has been demonstrated to have a negative impact on intimate relationships, quality of life 8 and self-esteem. 9 Although the etiology of ED is complex and understood to be the result of interplay between altered erectile nerve function, cognitive decline, illness-related stress and decreased interpersonal interaction, 10,11 both the pathology of ED and dysthyroidism have been highlighted as sharing common underlying endocrine dysfunction.…”
Section: Introductionmentioning
confidence: 99%